Mass Perception about Music during Lockdown in Nepal: A Case of Fine Arts Campus - Parsuram Prasad Poudel (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Engaging along with music during lockdown is a kind of common behavior of human beings. This article mirrors the mass perception of music during the specific situation of lockdown in Nepal. The descriptive online survey design was used by taking 136 participants from Fine Arts Campus by purposive sampling technique. Frequency, percentage, and presentation of chars were major statistical techniques used in this research. The finding indicates that most of the participants were enjoying by listening and participating in musical activities during the pandemic. Whatever the purpose of listening, singing, dancing, composing, recording, playing the musical patterns, mass people knowingly-unknowingly connected with music during a lockdown. So, concluded that almost all respondents voted for the need for musical activities and varieties of music for managing their stress.